A novel anti-viral role for STAT3 in IFN-α signalling responses. - Stevenson, Nigel; Bowie, Andrew; Roberts, Kim; Bourke, Nollaig; O'Farrelly, Cliona (Springer, 2017)
The cytokine, Interferon (IFN)-α, induces a wide spectrum of anti-viral mediators, via the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway. STAT1 and STAT2 are well characterised to upregulate IFN-stimulated gene (ISG) expression; but even though STAT3 is also activated by IFN-α, its role in anti-viral ISG induction is unclear. Several viruses, including Hepatitis C and Mumps, reduce cellular STAT3 protein levels, via the promotion of ubiquitin-mediated proteasomal degradation. This viral immune evasion mechanism suggests an undiscovered anti-viral role for STAT3 in IFN-α signalling. To investigate STAT3’s functional involvement in this Type I IFN pathway, we first analysed its effect upon the replication of two viruses, Influenza and Vaccinia. Viral plaque assays, using Wild Type (WT) andSTAT3-/- Murine Embryonic Fibroblasts (MEFs), revealed that STAT3 is required for the inhibition of Influenza and Vaccinia replication. Furthermore, STAT3 shRNA knockdown also enhanced Influenza replication and hindered induction of several, well characterised, anti-viral ISGs: PKR, OAS2, MxB and ISG15; while STAT3 expression had no effect upon induction of a separate ISG group: Viperin, IFI27, CXCL10 and CCL5. These discoveries reveal, for the first time, an anti-viral role forSTAT3 in the IFN-a pathway and characterise a requirement for STAT3 in the expression of specific ISGs. These findings also identify STAT3 as a therapeutic target against viral infection and highlight it as an essential pathway component for endogenous and therapeutic IFN-a responsiveness.
PUBLISHED
Keywords: Janus kinase/signal transducer of activator of transcription(JAK/STAT); STAT3; IFN-stimulated gene (ISG); Vaccinia virus; Influenza virus; Anti-viral; Interferon-alpha (IFN-α); Immunology, Inflammation & Infection